Pengaruh Ukuran Partikel Beberapa Insektisida Terhadap Efektivitas Dalam Aplikasinya - Djumarman Djumarman (Balai Besar Kimia dan Kemasan, 1987)
The importance of particle size in relation to activity have been reviewed. Studies with DDT indicated that there is an inverse relationship exists between the DDT crystal size and effectiveness. Field tests with chlorpyrifos showed that finer particled wettable powder were more active againts the cotton bollwonn than the larger particles which formed on the plant from emulsion sprays. But, control of codling moth with chlor pyrifos showed that a larger particled wettable powder remains toxic to just inster larvae for longer than finer particles. Other experiments showed that first inster larvae of cabbage white Butterfly picked up and dropped tha largest particles of carbaryl, whilethe smallest adhere too strongly to the plant surface.